Pengaruh Nilai Ekspor dan Pendapatan Domestik Bruto Indonesia terhadap Nilai Kurs Mata Uang Rupiah (IDR–USD) - Dodi Irwan Siregar (Jurnal Ekonomi KIAT, 2018)
As explained in the Mundell-Fleming theory (Mankiw, 2006), which states that there is a negative influence between the exchange rate and economic growth, where the higher the exchange rate, the net exports (the difference between exports and imports) are lower, this decline will have an impact on the amount of output decreasing and will cause GDP (economic growth) to decline. Export is the process of transporting goods or commodities of a country to another country, this process is often used by companies with small to medium scale businesses as the main strategy to compete at the international level. This study uses multiple linear regression analysis to predict and predict changes in the value of certain variables when other variables change. Correlation is one of the statistical analysis techniques used to find relationships between two or more variables that are quantitative. By using linearity test where f counts > f table is 20,4185 > 6,944 So, Ho is rejected. Where multiple linear regression analysis can be used to analyze the effect of Indonesia’s Export Value and Gross Domestic Product on the Value of the Rupiah Currency Exchange (IDR-USD). Obtained the multiple linear regression equation is Y = 4114.9996434 - 9.54927X1 + 0.9247X2, Interpretation of the correlation (linkage) of the relationship between IDR-USD (Y) Currency Exchange Variables to Indonesian Export Value (X1) and Domestic Products Gross (X2) is 0.954352126 with a very strong interpretation which ranges from 0.75 to 0.99.